Sistem Pendukung Keputusan Pemilihan Tempat Kost Mahasiswa Menggunakan Metode Saw (Simple Additive Weighting) - Muhammad Daffa Sumarto; Winny Purbaratri; Dwi Atmodjo Wismono Prapto; M. Isnin Faried (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2023)
Boarding homes are very crucial for students who live far from home, especially for those who go to Perbanas Institute. Choosing a boarding home has frequently been done without a defined procedure, which has made it hard for students to identify alternatives that fit their needs and budget. This study creates a web-based decision support system (DSS) for choosing boarding homes based on the Simple Additive Weighting (SAW) technique. This technique gives each criterion price, distance to campus, facilities, security, and room size weights. These weights are then used to find the best option from the 10 available by normalizing and ranking them. Surveys, observations, and reading books were used to gather research data. The weights were then set depending on what the students wanted. The results of the calculations reveal that "Kost Evi" got the highest score, hence it is the best pick. The system that was created can make decisions faster and easier, and it does it in a way that is clear and accurate. This technique may also be used in a number of different multi-criteria decision-making situations, making it a useful and adaptable option for more organized decision-making needs...